Analisis Fraud Triangle untuk Mendeteksi Financial Statement Fraud: Studi Empiris pada Perusahaan Properties & Real Estate yang terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Nafisa Athiyya Ramadhani; Kurniawati, Lintang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to obtain empirical evidence on the influence of the Fraud Triangle in detecting Financial Statement Fraud. Seven independent variables were used in this study. These seven variables are derived from three elements of fraud triangle: Financial Stability, External Pressure, Personal Financial Need, Financial Target (from the pressure), Nature of Industry, Ineffective Monitoring (from the opportunity), and Auditor Changes (from the rationalization). Meanwhile, the dependent variable, Financial Statement Fraud, was obtained using the Beneish M-Score. The population of this study was property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. Sampling was conducted using purposive sampling, resulting in 27 companies with three years of observation. This resulted in a total of 81 samples. This research hypotheses were then tested by using binary logistic regression analysis with SPSS 27 software. The result of this study indicate that External Pressure and Auditor Changes influence Financial Statement Fraud. Meanwhile, Financial Stability, Personal Financial Need, Financial target, Nature of Industry, and Ineffective Monitoring did not affect Financial Statement Fraud.